Sussuarana: Entre identidades, memórias e resistências quilombola que persistem na luta pela propriedade da terra, em Piripiri-PI (1996-2023) - SILVA, Jean Paulo Nascimento (2024)
The research investigates the rural quilombola community of Sussuarana, located in the municipality of Piripiri, state of Piauí, problematizing how contemporary social movements are important for an effective organization of these communities called quilombo remnants. The community under study declares itself as quilombola under the terms of Decree 4887, of November 20, 20031. Thus, the aim is to analyze the discourses and practices that make up the process of formation and organization of this community, as well as to investigate the identity of the subjects who live in or are involved with this location. The research is necessary because it aims to contribute to the problematization, information and, mainly, it strives to record and/or analyze the voice of the residents involved with the place under study. This community was certified by the Palmares Cultural Foundation - FCP in 2017. The identification and recognition process, briefly presented, should be analyzed based on its historical relationships. To this end, a survey was conducted on its ancestry and the characters who lived there, the foundation of the residents' association, cultural manifestations, the organization in favor of certification and land titling, etc. Before doing so, however, it is essential to understand what a quilombola community is in contemporary times and the due appropriation of the processes of struggle over time in Sussuarana, especially the process of titling their lands, which was still ongoing at the time of the research. To materialize this research, a bibliographic review was used and it is mainly based on the oral history methodology that guided the collection of sources for writing this dissertation. The reports collected through interviews constitute the main source of the documentary corpus of historical scientific research which was joined by other documents, such as: the Federal Constitution of 1988, in its Act of Transitional Constitutional Provisions in its art. 68; Decree 4887, of 2003; articles from websites about the community under study, photographic records, as well as specialized works by authors who address key concepts for the development of research such as identity, memory, territoriality, culture, representation, invention of tradition, such as: POLLACK (1989), NORA (1993), RICOEUR (2007), SANTANA (1984), KOSSOV (2012), SANTIROCCHI (2010), BOURDIEU (2008), HALL, LEITE (2000) E (2008), HOBSBAWM (1997), THOMPSON (1981), ALBERTI (2010), ARRUTI (1997), FREITAS (2006), FIABANI (2007), O’DWYER (2002), LOPES (2009) GOMES E REIS (2012), among others. The research has great social relevance, as it is a contemporary historical investigation into remaining quilombola communities, found, most of the time, in rural areas far from large cities, making the struggle of the various remaining quilombola peoples in Brazil a social organization that seeks the right to legal occupation of land, the valorization and preservation of their cultural manifestations, the right to be authors of their own history, making them and these places living and resilient communities that seek self-affirmation and recognition of their ethnic origins and a collective memory that refers to slavery.